Space standards that apply to the construction of social housing: a comparison between Portugal and the municipality of São Paulo - Pedro, João Branco (Universidade de São Paulo. Faculdade de Arquitetura e Urbanismo., 2012)
This article compares the space standards that apply to theconstruction of social housing in Portugal and in the municipality ofSão Paulo and seeks explanations for the identified differences inthe socioeconomic context of each territory. The Controlled CostHousing (CCH) program from Portugal and the My Home My Life(MHML) program in São Paulo are investigated.The space standards are more stringent for CCH than for MHML.The less-stringent space standards in the municipality of São Paulomay be justified by the housing deficit that exists in Brazil, the lowincome of poor households, and the option to sell highly subsidizedaffordable housing. Although affordable homes are substantiallysmaller in the municipality of São Paulo, user satisfaction withdwelling size is higher.Based on the results of this study, these authors recommendconducting an examination of the feasibility of several improvementsto the MCMV program. The following improvements should beconsidered: increase the total floor area of the dwellings; encourageinnovative spatial and construction solutions that are economic andcomply with the user needs; enable the construction of dwellingswith one, two, three, or four bedrooms; and increase the return onpublic investment with more sustainable economic models.